If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -54 = 9(g + -97) Reorder the terms: -54 = 9(-97 + g) -54 = (-97 * 9 + g * 9) -54 = (-873 + 9g) Solving -54 = -873 + 9g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-9g' to each side of the equation. -54 + -9g = -873 + 9g + -9g Combine like terms: 9g + -9g = 0 -54 + -9g = -873 + 0 -54 + -9g = -873 Add '54' to each side of the equation. -54 + 54 + -9g = -873 + 54 Combine like terms: -54 + 54 = 0 0 + -9g = -873 + 54 -9g = -873 + 54 Combine like terms: -873 + 54 = -819 -9g = -819 Divide each side by '-9'. g = 91 Simplifying g = 91
| 1/2COS^2(5X) | | 75=1/3(3.14)(4^2)H | | h(4^2)(3.14)1/3 | | 68=7(x+4)+5 | | 8a-3=6a+12 | | 21x^2-x^4-80=0 | | -5.91x=-42.14421 | | 4.4y+7.1=6.4y-6.6 | | 8x=0.67 | | 4.7x+8.7=-10.1 | | 6log((x^2)+1)-x=0 | | 8x+xy=1 | | X^2+y^2+10x-4y+20=0 | | 8q-1=72 | | 8x+yx=1 | | -0.2x+5.29=-0.4x+2.69 | | 2(-3)-4(-4)=20 | | 8x+x=1 | | 700x-0.25=500x+0.49 | | y=.4x^(2/3) | | (10x-2)(x-1)=10 | | (2m+5)+2(m-3)=11 | | 4.5x+10-6.5x=8 | | 0.5x+0.6=-0.9 | | 6x+8.26=3x+13 | | 2=10(x+4)+2x | | 6.1x=-23.18 | | -8y=4.88 | | 45=3/2z | | 5y-7z=14 | | 5x-11y=8 | | -4/5p=32 |